Brand Lokal Produk Pariwisata Maluku Utara: Upaya Konservasi Bahasa Daerah - Halida Nuria; Rahma Do Subuh (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Post-pandemic economic recovery focuses on developing the tourism sector through revitalizing tourist objects and developing tourism-based MSMEs. This can be seen by the proliferation of MSMEs by sharing superior products. On the one hand, tourism development has a positive impact by increasing regional income, especially through foreign tourist visits. But on the other hand this policy can have a negative impact on the preservation of regional languages. Therefore tourism development policies must be balanced with regional language maintenance policies. This problem can be overcome with policies to use regional languages or local terms as tourism product brands. The use of local brands for tourism products can be a means of maintaining local languages. This study aims to analyze various languages or local terms used by tourism business actors in various tourism products as a form of language conservation. The use of qualitative descriptive methods with observation, interviews and documentation techniques to identify various tourism products that use local terms as brands, brands or labels in their marketing. In addition, the background and meaning of the various local terms are also traced to obtain comprehensive data. From several districts and cities in North Maluku, many business actors and tourism managers choose to use local terms as brands or product brands because of the philosophy or story telling in these local terms.